FGM: challenges for asylum applicants and officials - Flamand, C (Refugee Studies Centre, University of Oxford, 2015)
Asylum authorities in the European Union need to establish better procedures to help address the specific vulnerabilities and protection needs of women and girls who have undergone or are at risk of female genital mutilation.